A clinical variant in SCN1A inherited from a mosaic father cosegregates with a novel variant to cause Dravet syndrome in a consanguineous family. - Tuncer, Feyza N; Gormez, Zeliha; Calik, Mustafa; Altiokka Uzun, Gunes; Sagiroglu, Mahmut S; Yuceturk, Betul; Yuksel, Bayram; Baykan, Betul; Bebek, Nerses; Iscan, Akin; Ugur Iseri, Sibel A; Ozbek, Ugur (My University, 2015)
A consanguineous family from Turkey having two children with intellectual disability exhibiting myoclonic, febrile and other generalized seizures was recruited to identify the genetic origin of these phenotypes. A combined approach of SNP genotyping and exome sequencing was employed both to screen genes associated with Dravet syndrome and to detect homozygous variants. Analysis of exome data was extended further to identify compound heterozygosity. Herein, we report identification of two paternally inherited genetic variants in SCN1A (rs121917918; p.R101Q and p.I1576T), one of which was previously implicated in Dravet syndrome. Interestingly, the previously reported clinical variant (rs121917918; p.R101Q) displayed mosaicism in the blood and saliva of the father. The study supported the genetic diagnosis of affected children as Dravet syndrome possibly due to the combined effect of one clinically associated (rs121917918; p.R101Q) and one novel (p.I1576T) variants in SCN1A gene. This finding is important given that heterozygous variants may be overlooked in standard exome scans of consanguineous families. Thus, we are presenting an interesting example, where the inheritance of the condition may be misinterpreted as recessive and identical by descent due to consanguinity and mosaicism in one of the parents.
Keywords: Compound heterozygosity; Dravet syndrome; Exome sequencing; Mosaicism; SCN1A